THEORETICALLY DEFINING THE GENDERED EMPOWERMENT AND QUOTA REPRESENTATION - Meena, Harsh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Democracies are seen as synonyms for political participation and representation. With the global wave of feminism, empowerment and political representation of women were seen as essential tools for delivering gender justice; they detected vulnerability based on gender. The aspect of empowerment is necessary to define the unequal power dynamics based on social gender norms. In contrast, political representation is seen as a way to reform the vulnerability. Feminism's recent global wave pushed the government to reconsider its patriarchal policies and accommodate the representation of women. The current paper looks into the various aspects of the women's empowerment and Representation debate.